Outcome of Endoscopic Transcanal Cartilage Myringoplasty performed in Janaki Medical College Teaching Hospital - Karmacharya, Sameer; Sah, Santosh Kumar (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: Myringoplasty is a commonly performed surgical procedure usually with a microscope. Transcanal endoscopic myringoplasty is being widely used procedures nowadays and has the advantages of demanding lower operative time and minimal external incisions. The main objective of our study was to see the graft uptake rate and hearing results after endoscopic cartilage myringoplasty. Material and Methods: This prospective study was carried out on 50 patients from March 01, 2020 till April 30, 2021. All patients presented with central perforation of tympanic membrane which was dry for at least 3 months were subjected to preoperative clinical, endoscopic, audiological assessment. These patients were followed through a period of 6 months and assessed using pure tone audiometry and graft uptake was seen. Results: Out of 50 patients, male: female ratio was 1.9:1 with mean age group of 34 years. In our study the graft uptake rates is 85% (42) and 6 patient has pin hole perforation and 2 has small central re-perforation on 6 month followup. Mean preoperative air bone gap was 28.95 dB whereas mean postoperative air bone gap was 10.63 dB. The maximum number of patient i.e 20 had pre-operative air bone gap in the range of 31 – 40 and 20 has post operative air bone gap in the range of 0-10 which is normal. Conclusions: The endoscopic approach for myringoplasty offers excellent visualization; avoids postaural approach, enables a faster recovery, requires less hospital stay, with excellent graft closure rate and improved functional outcomes.